IMPLEMENTASI BIMBINGAN DAN KONSELING KELOMPOK BERBASIS PUASA DALAM MEREDUKSI PRILAKU PENYALAHGUNAAN NAPZA - azhari, azhari (Hisbah: Jurnal Bimbingan Konseling dan Dakwah Islam, 2023)
Fasting has a lot to do with training or riyadhah (exercise) or the biggest training for oneself to earnestly go to and draw closer to Allah, where spiritual practice has an effect on physical and mental balance. Fasting also answers how to form a positive mentality. A Muslim begins his fast with the intention for Allah until he gets a balance of thoughts, feelings and behavior. As Allah says in surah al-Baqarah 183; Meaning: O you who believe, fasting is prescribed for you as it was prescribed for those before you so that you may be pious. So along with the development of science, fasting is used as a therapeutic value, relaxation and counseling. including the Pintu Hijrah Banda Aceh foundation, which has made a breakthrough in providing special attention to Residents who commonly commit drug abuse in order to minimize this habit by formulating and implementing it through the dynamics of group counseling (group counseling) based on fasting. This research focuses on how drug abuse behavior, the implementation of fasting-based group guidance and counseling and the obstacles faced by counselors in implementing fasting-based group guidance and counseling services to reduce drug abuse behavior. The approach in this study uses interpretive with descriptive characteristics and tends to use analysis. The method used uses the phenomenological method where the researcher tries to work on a phenomenon that occurs but needs to be understood seriously to find answers to the questions that exist in this phenomenon through the application of scientific procedures in a systematic manner. data collection techniques through: observation, document analysis and interviews. The results showed that the implementation of fasting-based group counseling was very effective for drug residents with a duration of sixty minutes in each session for forty-eight sessions or six months in one rehabilitation period. observation, document analysis and interviews. The results showed that the implementation of fasting-based group counseling was very effective for drug residents with a duration of sixty minutes in each session for forty-eight sessions or six months in one rehabilitation period. observation, document analysis and interviews. The results showed that the implementation of fasting-based group counseling was very effective for drug residents with a duration of sixty minutes in each session for forty-eight sessions or six months in one rehabilitation period.   Keywords: Group Guidance and Counseling, Fasting, Drug Abuse Behavior.